ANALYSIS OF COMMUTER LINE TICKET PURCHASE QUEUING SYSTEM IN BOGOR STATION - Resista Vikaliana (STIE Binaniaga, 2017)
Queue is a situation that happen to people, goods, and components that need to wait to get a service. The good quality of service will satisfy the customers and decrease the queue line. Queue often happens in a station especially in weekdays. A long queue line happens in the station is one of the problems that need to be solved. Instead of manual ticket purchasing that served by the operator, today PT KAI Commuter Line also serve ticket purchasing using THB machine. The purpose of this study is to compare the performance of queuing model that happen in Bogor station locket and to determine if the queuing model is efficient by comparing the service standard, between the manual and the one that used THB machine. The method used in this research was descriptive method by using queuing theory calculation. The model of locket queuing using THB machine in Bogor Station is Multi Channel-Multi Phase, in ticket purchasing using THB machine. Besides, in the operator locket service, the queuing model is Single Channel-Single Phase. Both s ticket purchasing service use First In First Out (FIFO) disciple. The maximum amount of the queue line and the source of customers’ arrival are infinite. Based on the value of system performance can be concluded that queuing system and the service given already great and effective (based on the performance measure and probability or passengers’’ chances), passengers who are waiting to buy tickets, either manual or using machine less than 1, or assumed 1 person. From the observation, the use of THB machine decrease the queue line, but need to be socialized because passengers does not know how to use THB machine to buy ticket independently.Keywords: queue, queuing model, commuter line ticket purchasing, Bogor station